Effects of process parameters on mechanical properties of micro selective laser melting- printed 316L stainless steel - Lee, Joseph Zhi Wei (2019)
Additive Manufacturing (AM) has been used mainly to produce macro-components in small to medium lot sizes. In view of the ever-growing demand for miniaturization, the focus is currently drawn towards fabricating micro and nanofeatures with AM. Selective Laser Melting (SLM) is one of the most common AM techniques based on powder bed fusion to fabricate metal components. However, conventional SLM is limited in areas such as surface quality which could be vastly improved through the scale down of the technique to micro-SLM. Possessing a faster cycle time and material versatility, micro-SLM could potentially substitute current direct writing methods used in micro AM. This project aims to understand the effect of process parameters in microscale SLM on the printed part characteristics to optimize micro SLM. Bulk and thin foil samples were fabricated by micro-SLM based on varying hatch spacing, laser power and scanning speed. The fabricated part quality was characterized through defects, porosity and surface morphology. The influence of the process parameters on the cross-sectional hardness was studied followed by the corresponding microstructure characterization to optimize the micro-SLM process and understand the process behaviors. For bulk samples, the correlation between process parameters and part characteristics were found to be largely similar to that of conventional SLM. One the other hand, thin foil samples with a minimum resolution of 50 um were produced which managed to achieve 100% part density. A correlation between process parameters and hardness was observed, differing from the conventional SLM. Microstructures of the samples were critical in the understanding of underlying correlations, which varies significantly based on the process conditions.